Hot carrier relaxation in CdTe via phonon–plasmon modes. (23rd January 2017) - Zhong, Y; Ostach, D; Scholz, M; Epp, S W; Techert, S; Schlichting, I; Ullrich, J; Krasniqi, F S
Abstract: Carrier and lattice dynamics of laser excited CdTe was studied by time-resolved reflectivity for excitation fluences spanning about three orders of magnitude, from 0.064 to 6.14 mJ cm −2 . At fluences below 1 mJ cm −2 the transient reflectivity is dominated by the dynamics of hybrid phonon–plasmon modes. At fluences above 1 mJ cm −2 the time-dependent reflectivity curves show a complex interplay between band-gap renormalization, band filling, carrier dynamics and recombination. A framework that accounts for such complex dynamics is presented and used to model the time-dependent reflectivity data. This model suggests that the excess energy of the laser-excited hot carriers is reduced much more efficiently by emitting hybrid phonon–plasmon modes rather than bare longitudinal optical phonons.